Eplerenone Reverses Cardiac Fibrosis via the Suppression of Tregs by Inhibition of Kv1.3 Channel - Shao, Pei-Pei; Liu, Chang-Jiang; Xu, Qi; Zhang, Bo; Li, Shao-Hua; Wu, Yang; Sun, Zhan; Cheng, Lu-Feng (Frontiers in Physiology, 2018)
Background: Fibroblast proliferation is a critical feature during heart failure development. Previous studies reported regulatory T-lymphocytes (Tregs)’s protective role against myocardial fibrosis. However, Treg is known to primarily secrete fibrogenic cytokine TGF-β followed by activation of Kv1.3, a potassium channel. This study aimed to clarify the intriguing link between Treg and fibrosis, and how eplerenone, a selective aldosterone receptor antagonist, affects Treg and fibrosis. Methods &Results: After co-incubation with Tregs, cardiac fibroblast proliferation (CCK-8 assay) and levels of collagen I, III, and Matrix metalloproteinase2 (ELISA) significantly elevated. Cell viability assays, Kv1.3 channel mRNA (RT-qPCR), and protein expression (In-Cell Western Blotting) revealed Tregs were activated/proliferated when co-cultured with fibroblasts. Treg intracellular TGF-β level increased by 5.8-fold, far more than that of intracellular IL-10, extracellular TGF-βand IL-10 (ELISA). And 30μM eplerenone suppressed Tregs proliferation by 82.77% and furthermore, suppressed intracellular TGF-β level to a significantly greater extent than that of intracellular IL-10, extracellular TGF-β and IL-10. Moreover, the Kv1.3 current (whole-cell patch clamp) of Tregs in congestive heart failure patients and rats (induced by coronary artery ligation and exhaustive exercise) elevated by >4-fold than that of healthy volunteers and control rats, whereas 30μM eplerenone suppressed the current by >60% in control Tregs. In addition, docking calculations (AutoDock software 4.0 suite) showed eplerenone has higher H-bond energy with Kv1.3 channel than other selective blockers. Conclusion: Immuno-regulation in the late stage of CHF activates Tregs proliferation via the upregulation of Kv1.3 channels, which promotes cardiac fibrosis by primarily secreting TGF-β. Taken together, eplerenone’s high affinity to Kv1.3 channel enables it to antagonize the Kv1.3 channels directly to suppress Tregs proliferation, which in turn may play an immuno-regulatory role during CHF.